Reflexo brasileiro em olhos mexicanos: O Brasil em Monterrey, correo literario de Alfonso Reyes - Alonso, Cecilia Laura (2006)
Alfonso Reyes, an outstanding mexican humanist from the 20th century, took the position of ambassador of Mexico in Brazil throughout seven years during the 30 s. He got strongly involved with the brazilian cultural life and became a friend of politicians, writers and famous artists. Although he had to cope with his diplomat responsibilities and his writer s desires, he was one of hispanic american writer who most produced in the country. In Rio de Janeiro, he published MONTERREY, correo literario de Alfonso Reyes, in which he could be in touch with brazilian intellectuals and foreigners. By showing Brazil through its culture, nature and people, Alfonso Reyes spurred a dialogue between the country and the Hispanic America.